Erythrocyte phenotyping of international athletes by flow cytometry - Renovato-Martin M.; Dudenhoeffer-Carneiro AC; Du Rocher-Silva B; Soares F; Aquino Neto FR; Mahbub, Hasan; Rahaman, Khandoker Asiqur; Muresan, Anca Raluca; KWON, Oh-Seung; Mirotti L; Pereira HM (Manfred Donike Workshop, 38th Cologne Workshop on Dope Analysis (2020.2.9-2.14), 2020)
Blood transfusion is performed by cheating athletes to rapidly increase oxygen delivery to exercising muscles and enhance their performance. Homologous blood transfusion happens when blood from a different person is transfused. The method used to detect this type of doping is based on flow cytometry, by identifying variations in blood group minor antigens present on erythrocytes surface. Different authors and anti-doping laboratories use different panels of erythrocyte antigens to allow the detection of mixed populations. In total, there are more than 300 different red blood cells antigens and the detection is based on the most abundant families, normally in a total of around 8- 10 antigens. It has been reported that number of occurrences of two individuals sharing an identical phenotype in the same population of athletes is 5 times higher than the theoretical probability. This work describes the data of athletes who were analyzed by flow cytometry for the prevalence of different erythrocytes surface antigens (C, E, Fya, Fyb, Jka, Jkb and S) in a population of 360 international athletes from all 5 continents.